2020
DOI: 10.1002/ange.201914967
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Vacancies that Boost Electrocatalytic Hydrogen Evolution by Two Orders of Magnitude

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Cu 2 O(111) and h-BN(002) slabs were first constructed as model systems of cubic Cu 2 O and hexagonal BN, respectively, matching the experimentally determined XRD planes (Figure 1a). [54] In contrast, the B 2p and N 2p states (Figure 5b) of Cu 2 OÀ BN differ markedly from those of h-BN. Combined with the right shift of the Cu 3d In other words, h-BN becomes slightly semi-conductive owing to electron transfer from Cu 2 O, which is similar to previous theoretical results wherein Ni-supported h-BN has slightly metallic properties.…”
Section: Methodsmentioning
confidence: 85%
“…Cu 2 O(111) and h-BN(002) slabs were first constructed as model systems of cubic Cu 2 O and hexagonal BN, respectively, matching the experimentally determined XRD planes (Figure 1a). [54] In contrast, the B 2p and N 2p states (Figure 5b) of Cu 2 OÀ BN differ markedly from those of h-BN. Combined with the right shift of the Cu 3d In other words, h-BN becomes slightly semi-conductive owing to electron transfer from Cu 2 O, which is similar to previous theoretical results wherein Ni-supported h-BN has slightly metallic properties.…”
Section: Methodsmentioning
confidence: 85%
“…7b and c). 155 Moreover, Barik et al confirmed that the presence of vacancies in monolayer MoS 2 could remarkably enhance the Li/Na-ion storage capability (Fig. 7d).…”
Section: The Effects Of Defects On Energy Conversion and Storagementioning
confidence: 87%
“…Copyright 2020, Elsevier Ltd. (b and c) Electron distribution (b) and 2D charge difference isosurface (c) of V P -modified Ni 12 P 5 nanosheets. Reproduced with permission 155. Copyright 2020, Wiley-VCH.…”
mentioning
confidence: 99%
“…Based on this assumption, it was deduced that for Cu 2 OÀ BN, the slight decrease in FE CO and FE C 2 H 4 in the ensuing 12 h (Figure 3f) was predominantly due to a partial reduction of the Cu + species to metallic Cu 0 . [35] However, for Cu 2 O, without the protection of the h-BN sheets, most of the Cu + species are [54] In contrast, the B 2p and N 2p states (Figure 5b) of Cu 2 OÀ BN differ markedly from those of h-BN. Combined with the right shift of the Cu 3d band, the significant left shift of the B 2p and N 2p energy states demonstrates electron transfer from Cu 2 O to h-BN and the existence of strong electronic interactions.…”
Section: Methodsmentioning
confidence: 97%